2015
DOI: 10.3389/fpls.2014.00779
|View full text |Cite
|
Sign up to set email alerts
|

Milestones in plant sulfur research on sulfur-induced-resistance (SIR) in Europe

Abstract: Until the 1970's of the last century sulfur (S) was mainly regarded as a pollutant being the main contributor of acid rain, causing forest dieback in central Europe. When Clean Air Acts came into force at the start of the 1980's SO2 contaminations in the air were consequently reduced within the next years. S changed from an unwanted pollutant into a lacking plant nutrient in agriculture since agricultural fields were no longer “fertilized” indirectly by industrial pollution. S deficiency was first noticed in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 75 publications
0
55
0
Order By: Relevance
“…The existence of a bi‐directional COS flux contradicts our initial expectation for COS uptake by astomatous bryophytes, because there are currently no described leaf‐level processes that result in COS as a byproduct (Protoschill‐Krebs et al ., 1996; Bloem et al ., 2015). Previously, Fried et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of a bi‐directional COS flux contradicts our initial expectation for COS uptake by astomatous bryophytes, because there are currently no described leaf‐level processes that result in COS as a byproduct (Protoschill‐Krebs et al ., 1996; Bloem et al ., 2015). Previously, Fried et al .…”
Section: Discussionmentioning
confidence: 99%
“…COS diffuses into the vegetation through the stomatal pores and is hydrolysed by the enzyme carbonic anhydrase (CA) in the mesophyll cells (Protoschill‐Krebs et al ., 1996). However, in contrast to CO 2 hydration by CA, COS hydrolysis by CA is irreversible (Notni et al ., 2007) and no other leaf‐level processes have been identified in the production of COS (Bloem et al ., 2015). Thus, COS uptake ( A S ) is assumed to be unidirectional and not the net result of two opposed fluxes (photosynthesis and respiration in the case of CO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, our results showed better protection against O. neolycopersici when the compound was applied as a preventive soil drench, suggesting that the protective effect of the bioassimilable sulphur may be related to the induction of plant defences. Previous studies have suggested that the application of sulphur can improve the natural resistance of plants against fungal pathogens through the stimulation of metabolic processes that involve S 0 , resulting in so‐called sulphur‐induced resistance (SIR) …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the application of sulphur can improve the natural resistance of plants against fungal pathogens through the stimulation of metabolic processes that involve S 0 , resulting in so-called sulphur-induced resistance (SIR). 20 Callose accumulation is a characteristic cellular response of early post-invasive defences that prevents the colonisation of the pathogen by creating a physical barrier at the site of the infection. This barrier is able to slow pathogen invasion in the attacked tissue, giving more time to activate additional defence responses that may require gene activation and expression.…”
Section: Discussionmentioning
confidence: 99%
“…(Cobbett, 2000;Cobbett and Goldsbrough, 2002), and reduced glutathione (GSH) involved in both metal chelation and in scavenging potential oxidative stress as a result of ROS production induced by Cr exposure ( Grill et al 2004;Panda, 2007;Upadhyay andPanda, 2010, Volland et al 2011). Hence sulfur availability can lead to an increased capacity to cope with biotic and abiotic stresses, a phenomenon known as SIR/SED (Sulfur Induced Resistance or Sulfur Enhanced Defence) (Bloem et al 2015;Ernst et al 2008;Höller et al 2010;Nazar et al 2011;Nocito et al 2006). Although a few reports suggest the involvement of PCs or MTs in Cr detoxification (Diwan et al 2010;Shanker et al 2004), two direct products of sulfur assimilation pathway other than PCs or MTs can be involved in chromium detoxification, since the metal can be sequestered through the formation of thiolate and cysteinthiolate complexes with glutathione and various derivatives of cysteine (Brauer et al 1996;Brauer and Wetterhahn, 1991).…”
Section: Introductionmentioning
confidence: 99%